Bayi Tabung Dalam Tinjauan Hukum Islam (Analisis Maqashid Syari’ah) - Irham Dongoran (Universitas Islam Negeri Sumatera Utara, 2020)
In every era, there are always social phenomena that arise, and Islamic law has covered and answered them for their legal position. One of the examples of the phenomena is IVF (In Vitro Fertilization), which is an artificial insemination as a shortcut to get children by bringing together sperm cells and egg cells outside the body which are then inserted into the mother's womb, so they can grow into a fetus as usual pregnancy. In this IVF process, there are likely to be 5 parties involved, namely: husband, wife, sperm donor, ovum donor and uterine mother. If there is a third party besides wife and husband involved in the process of IVF, there will be indications of genetic mixing in the fetus.IVF with a system without any third party involvement (sperm and ovum from husband and wife) by transferring into the womb of the wife is permissible and the baby is the descendant of his parents. However, if there is involvement of a third party, it is prohibited. IVF In the concept of Maqashid Shari'ah is one of the media that contributes in realizing 1. Hifdzu ad-din (protecting religion), 2. Hifdzu an-nafs (protecting souls), 3. Hifdzu al-aql (protecting the mind), 4. Hifdzu al-mal (protecting property), 5. Hifdzu an-nasab (protecting descendants). However, IVF is more dominant and looks more transparent in the aspect of Hifdzu an-nasab (protecting desdendants).